Peranan Konsep Diri Dan Efikasi Diri terhadap Burnout Academic pada Siswa di Masa Pandemi Covid-19 (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This study is conducted to examine the role of self-concept and self-efficacy on academic burnout in students. The method of research used in this study is a quantitative approach. The object of the research focuses on a sample of 278 students and uses the proportionate stratified random sampling technique. This research instrument uses an adaptation scale with a Likert model on academic burnout, self-concept, self-efficacy. The academic burnout scale was obtained from the Maslach Burnout Inventory-Student Survey (MBI-SS) which has been translated into Indonesian with a Cronbach's Alpha reliability of 0,838. The self-concept scale was adapted from self-concept in preadilescence: a brief version of AF5 (Five-Factor Self-Concept) scale with Cronbach's Alpha reliability of 0,825. The self-efficacy scale was adapted from the Self-Efficacy Questionnaire in Youth with Cronbach's Alpha reliability of 0,988. Furthermore, data analysis in this study uses multiple linear regression. The results of the study conclude that self-concept and self-efficacy have a big role in provoked academic burnout. It shows that students will experience less burnout when they feel confident to face all of the academic activities or when they can accomplish academic achievement. The contribution that is given together produces 30.5%. Self-concept contributes 12.99% while self-efficacy contributes 17.49%. So, we can conclude that self-efficacy contributes an important role in affecting academic burnout.